2020
DOI: 10.1038/s41467-020-14364-3
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Rabi splitting of a dark plasmonic cavity mode revealed by fast electrons

Abstract: Recent years have seen a growing interest in strong coupling between the electromagnetic modes of plasmonic structures and quantum emitters, as a way to generate new quantum optical testbeds and influence chemical dynamics and reactivity. Strong coupling involving bright plasmonic modes has been achieved in the limit of single quantum emitters. Dark plasmonic modes might fare better in some applications due to their longer lifetimes, but are difficult to probe as they are subradiant. Here, we apply electron en… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 39 publications
1
70
0
1
Order By: Relevance
“…(66,67)), to phonons in the mid-IR range. Similar methodologies are key to understanding the nanoscale behavior of mixed photon-matter excitations in different strongly coupled systems (68,69).…”
mentioning
confidence: 99%
“…(66,67)), to phonons in the mid-IR range. Similar methodologies are key to understanding the nanoscale behavior of mixed photon-matter excitations in different strongly coupled systems (68,69).…”
mentioning
confidence: 99%
“…The ability to strongly couple quantum emitters to individual PCs has aroused much excitement in recent years 16 19 . Our lab 20 , 21 and others’ 22 – 25 have demonstrated that such a strong coupling can be realized even in the limit of a single semiconductor nanocrystal (quantum dot, QD) or molecule, and can be observed as vacuum Rabi splitting in light scattering, photoluminescence (PL) or electron energy loss spectra of the coupled systems. Plasmonic cavities with coupled quantum emitters may serve as new testbeds for studies of quantum optical and chemical dynamics under ambient conditions.…”
Section: Introductionmentioning
confidence: 95%
“…With augmenting the coupling strength continuously, the rate of energy transfer will overwhelm their attenuation rate, [26] and hence the strongly coupled interaction occurs, featuring the half-light and halfmatter characteristics. [27] Subsequently, the resulted Rabi splitting [28] divides the archetypal eigenstates into two new polaritonic states, namely the upper and lower polariton, respectively. [29,30] It is the exchange of energy that leads to an inimitable avenue to modify the energy landscape in the strongly coupled system completely.…”
Section: Introductionmentioning
confidence: 99%